Cloud Computing Loading Time Over Different Operating Systems - Faraj, Kamaran H.A; Kanbar, Asan B.; Gul-Mohammed, Jaza; Hmeed, Wafaa M.; Karim, Shagul F. (Science Journal of University of Zakho, 2020)
Since the traditional time loading (TTL) very primitive before the era of information communication technology (ICT) and it was really not depended on the result of time-loading due to the old version of computer architecture (i.e. serial processing). Nevertheless, the parallel processing systems open a wide area of researching for electronic time loading (ETL) over different operating systems by programing languages (i.e. python or private home page (Php)). The electronic time loading (ETL) for cloud Computing (CC) is a hot experimental topic. ETL for CC is not only one parameter (i.e. a web technologies type or a web applications type or an infrastructures type or an architectures type). Moderately, the term CC refers to the evolution of the information technology (IT). As we realized the ETL is very important for reducing time wasting. The reducing time-waste loading over different web operating systems or CC is a target in this paper. Finally, this paper test the Electronic Loading Time of CC over different operating systems with different types of network (i.e. public and private) discovering the least ETL. Hence the benchmarking TTL is not applicable (N/A) due to the activity from a person to others is very changeable and not depended on it at all. This paper shows the total time and load time over different OS in seconds, and find out the least time loading required this work is a good solution of the response time over different operating system in open source-LOS and non-open source WOS.